2019
DOI: 10.1177/1053451219842197
|View full text |Cite
|
Sign up to set email alerts
|

Self-Regulated Strategy Development to Teach Mathematics Problem Solving

Abstract: Many secondary students with specific learning disabilities (SLD) struggle with mathematics problem solving. When students with SLD are taught to use effective problem-solving strategies, their ability to solve mathematics word problems improves. The purpose of this article is to provide a guide for secondary teachers to implement self-regulated strategy development (SRSD) to teach mathematics problem-solving strategies to secondary students with SLD. The specific problem-solving strategy described in this art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
(28 reference statements)
0
6
0
2
Order By: Relevance
“…Studies have shown that self-regulated learning has a significant impact on students’ academic achievement (EI-Adl & Alkharusi, 2020 ). Students with high self-regulation learning level have good cognitive and metacognitive strategies, can make full use of external resources in the learning process, constantly monitor the distance from the goal, maintain a high level of learning efficacy, and effectively solve problems (Popham et al, 2020 ). In addition to this, self-regulation learning is a cyclical process that affects an individual’s cognitive development ability (Eissa, 2015 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies have shown that self-regulated learning has a significant impact on students’ academic achievement (EI-Adl & Alkharusi, 2020 ). Students with high self-regulation learning level have good cognitive and metacognitive strategies, can make full use of external resources in the learning process, constantly monitor the distance from the goal, maintain a high level of learning efficacy, and effectively solve problems (Popham et al, 2020 ). In addition to this, self-regulation learning is a cyclical process that affects an individual’s cognitive development ability (Eissa, 2015 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Self-regulated strategy development (SRSD) framework used by Popham et al (2020) to guide teachers to teach SOLVE method is an instructional framework, which includes use of "explicit instruction, cognitive strategy instruction, self-regulation instruction, and mnemonics to assist students in remembering steps in a process" (p. 2). This strategy in framework contain explicit instructions to develop metacognition of students.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Problem solving has, for some time, occupied a prominent position in education research (e.g., Lawson, 2003;Felmer et al, 2016;Priemer et al, 2020). In recent years, incorporating problem solving in school mathematics instruction has become a major area of interest within the field of mathematics education (e.g., Jitendra et al, 2005;Popham et al, 2020). From the perspective of teaching, research on the cognitive level has not been properly transferred to pedagogical issues, and remains separate from practice.…”
Section: Introductionmentioning
confidence: 99%